(untitled) (Journal of Dhaka Medical College, 2023)
Background: Preeclampsia and eclampsia is associated with a risk of abnormal hemostasis that occurs most commonly secondary to thrombocytopenia. Automated analyze technique measures whole blood coagulation and has been used to manage coagulation defects in obstetric patients. Objective: To find out the alteration of coagulation profile beyond physiological level in preeclampsia and eclampsia patients for early detection and planning of management. Method: It was a observation type of cross sectional study carried out Department of Obs& Gynae, Dhaka Medical College Hospital, Dhaka. Severe pre-eclamptic and eclamptic patients admitted in the department of Obstetrics &Gynaecology, Dhaka Medical College Hospital during the period of July 2018 to December 2018. Data were collected as predesigned data collection sheet and for coagulation profile. Collection of venous sample about 5ml of blood were done without a pressure cuff allowing the blood to enter the syringe by continuous free flow and sending to the laboratory for coagulation assay by automated analyzer Sysmex CA500. Results: In this study mean age was 26.94 years, majority 56% age group was 26-30 years of age. The mean gestational age was 32.36 weeks. All the coagulation parameters were altered in 6% of the patients, 4 parameters were altered in 10% of the patients, 3 parameters were altered in 16% of the patients 2 and 1 parameters were altered in 24% and 44% patients respectively. Regarding coagulation profile, thrombocytopenia was present in 22% patients, prothombin time was prolonged in 10% of the patients, APTT was prolonged in 20% of the patients, and fibrinogen level was reduced in 40% of the patients and FDP was elevated 32% of the patients. Out of 50 severe preeclamptic and eclamptic patients, 6% of the patients developed DIC in whom all the coagulation parameters were altered. Conclusion: In this study, in patients of severe pre-eclampsia and eclampsia 22% patients had thrombocytopenia. 6% of the patients had alteration of all the coagulation parameters. Coagulation indices were altered not only in the patients with reduced platelet count but also in the patients with normal platelet count. Among the patients, 6% of the patients developed DIC, PPH developed in 12% of the patients and maternal death occurred in 4% of the patients. J Dhaka Med Coll. 2021; 30(2) : 214-219